THU0547 Real-world effectiveness of early aggressive treatment with biological disease-modifying antirheumatic drugs for the treatment of newly diagnosed polyarticular form of juvenile idiopathic arthritis. (12th June 2018) - Huang, B.; Morgan, E.M.; Chen, C.; Guo, J.; Lovell, D.J.; Brunner, H.I.; ,
Abstract : Background: Limited evidence from randomised clinical trial suggested early aggressive treatment with biological disease modifying antirheumatic drugs (DMARDs) maybe a better treatment strategy in children with polyarticular form of Juvenile idiopathic arthritis(pJIA). 1 Three consensus treatment plans (CTP) were recommended for treating children with newly onset of pJIA. 2 The real-world effectiveness is unknown. Objectives: Evaluate the comparative effectiveness of early combination CTP vs. the step-up CTP, in treating children with newly diagnozed pJIA, utilising electronic health records (EHR) data collected from routine clinical care. Methods: This inception cohort is derived from data captured in a single institute EHR from January 2009 to July 2017. Eligible patients are 2–16 years of age, newly (<6 m) diagnosed with pJIA and treated on DMARD. The first clinical encounter initiate DMARDs is identified as the baseline. The primary end point is clinical Juvenile Arthritis Disease Activity Score (cJADAS) 6 months after the treatment. Results: Out of 1834 pJIA patients captured in EHR, 432 are eligible for the study. Most patients (362, 84%) initiated DMARD within 6 month of diagnosis: 105 (29%) on early combination and 257 (71%) on step-up plan. Three months following the initial DMARD assigment, 98 (93%) and 244 (95%) remained on the inital early combination and step-up plan respectively, thus are used in this study Patients on early combination had significantly higher cJADAS score at the baseline (15.5±6.6 vs. 12.5±5.9; Student P value<0.01), and higher rate of RF (18% vs. 7%, Chisq p<0.01). After 6 months of treatment, their cJADAS scores are more comparable (mean ±SD of 6.9±5.4 in early combination, and 7.1±6.1 in step-up; Student T p=0.7). After statistically adjusting for treatment selection bias, causal inference methods suggest lower cJADAS is expected had the patient been treated on early combination than on the step-up plan, mean and 95% confidence interval of averaged treatment effect is 2.90 (0.89, 4.91). Conclusions: The early combination approach improves clinical outcomes at 6 months more effectively than the step-up strategy in children with newly onset pJIA. References: [1] Wallace CA, Ringold S, Bohnsack J, Spalding SJ, Brunner HI, Milojevic D, Hendrickson A. Extension Study of Participants from the Trial of Early Aggressive Therapy in Juvenile Idiopathic Arthritis. The Journal of Rheumatology2014;41(12):2459–2465. https://doi.org/10.3899/jrheum.140347 [2] Ringold S, Weiss PF, Colbert RA, Dewitt EM, Lee T, Onel K, Kimura Y. Childhood arthritis and rheumatology research alliance consensus treatment plans for new-onset polyarticular Juvenile idiopathic arthritis. Arthritis Care and Research2014;66(7):1063–1072. https://doi.org/10.1002/acr.22259 Acknowledgements: Funding Support from PCORI, ME-1408–19 894 (PI, Huang) Disclosure of Interest: None declared